2016
DOI: 10.3390/ijms17111913
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Non-Tuberculous Mycobacteria Infection in Bronchiectasis

Abstract: Chronic airway infection is a key aspect of the pathogenesis of bronchiectasis. A growing interest has been raised on non-tuberculous mycobacteria (NTM) infection. We aimed at describing the clinical characteristics, diagnostic process, therapeutic options and outcomes of bronchiectasis patients with pulmonary NTM (pNTM) disease. This was a prospective, observational study enrolling 261 adult bronchiectasis patients during the stable state at the San Gerardo Hospital, Monza, Italy, from 2012 to 2015. Three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 26 publications
4
61
1
Order By: Relevance
“…When performed, the results indicated a low level of NTM with a higher proportion of non‐MAC mycobacteria seen in Aboriginal Australians. This was consistent with previous studies that found NTM isolated in 8–12% of patients and MAC in 4% …”
Section: Discussionsupporting
confidence: 94%
“…When performed, the results indicated a low level of NTM with a higher proportion of non‐MAC mycobacteria seen in Aboriginal Australians. This was consistent with previous studies that found NTM isolated in 8–12% of patients and MAC in 4% …”
Section: Discussionsupporting
confidence: 94%
“…Bronchiectasis and NTM are highly associated pulmonary diseases with airway distortion predisposing to NTM infection [79,80]. While NTM is isolated from the bronchiectasis airway and clearly associates with poorer outcomes and more aggressive disease in most cases (largely dependent on the species involved), in some studies, it interestingly has been associated with a milder phenotype, less severe disease, lower exacerbations and better pulmonary function [81,82]. NTM colonisation in common with P. aeruginosa is more frequent in older patients with gender preponderance for postmenopausal women and a lower prevalence is observed in paediatric populations [82][83][84][85].…”
Section: Geographic Variation In the Microbiology Of Bronchiectasis Tmentioning
confidence: 99%
“…NTM belonging to the MAC group are also highly prevalent in non-CF bronchiectasis with a female preponderance [35,36]. This group of organisms are surprisingly poorly associated with disease severity and exacerbations in the non-CF setting when compared to Pseudomonas [37,38]. In contrast for CF patients, MAC and M. abscessus are often associated with an aggressive and accelerated lung function decline [39][40][41][42].…”
Section: Microbiologymentioning
confidence: 99%